2016
DOI: 10.1016/j.jvs.2015.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-coated versus plain balloon angioplasty in the treatment of infrainguinal vein bypass stenosis

Abstract: Paclitaxel-coated and plain angioplasty of significant infrainguinal vein bypass stenoses performed equally well in clinical and hemodynamic improvement and in primary and assisted primary bypass patency rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…As the present series consisted of grafts with mainly non-reversed and in situ configurations, it is possible that certain situations such as retained valves causing graft failure might not be applicable to series with reversed saphenous vein grafts. Primary patency rates, assisted primary patency rates and in some series, secondary patency rates reported by Linni et al, 15 Ali et al, 10 van Oostenbrugge et al, 9 San Norberto et al, 16 Mofidi et al, 17 and Carlson et al 18 are summarized in Table 4. Apart from the present study, Linni et al 15 were the only others to report long-term outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the present series consisted of grafts with mainly non-reversed and in situ configurations, it is possible that certain situations such as retained valves causing graft failure might not be applicable to series with reversed saphenous vein grafts. Primary patency rates, assisted primary patency rates and in some series, secondary patency rates reported by Linni et al, 15 Ali et al, 10 van Oostenbrugge et al, 9 San Norberto et al, 16 Mofidi et al, 17 and Carlson et al 18 are summarized in Table 4. Apart from the present study, Linni et al 15 were the only others to report long-term outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Since the study period, drug-coated balloon angioplasty has been used at the study institution in recurrent graft stenosis. In this regard, Linni et al 15 concluded that paclitaxel-coated balloon angioplasty performed equally well to plain balloon angioplasty but randomized trials will be required to validate this finding. The use of bare and covered stents as a bailout option in infrainguinal vein grafts has been found to be safe with acceptable short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…DCB with anti-proliferation agents, such as paclitaxel or everolimus, was approved for femoropopliteal lesions in Japan in 2017 according to evidence from some randomized trials that demonstrated the superiority of DCBs over POBA in treatment [9][10][11][12][13][14][15][16]. However, the effect of DCBs on vein bypass grafts is controversial; Bjorkman et al showed a trend in favor of DCBs in bypass grafts [5], but other reports did not demonstrate the superiority of DCBs over POBA [6][7][8]. As there are various causes of graft failure, these studies might lack the patient cohort volume to reveal a drug effect on IH.…”
Section: Discussionmentioning
confidence: 99%
“…The drug-coated balloon (DCB) has recently emerged and is expected to be a powerful tool in replacing POBA as it can achieve excellent outcomes, including increased limb salvage rate or amputation-free rate in the treatment of femoropopliteal lesions, which has recently been reported. However, there are only a few reports suggesting that DCB is beneficial for bypasses using autogenous grafts [5][6][7][8]. Among the various methods of improving the patency, the effect of antiproliferative drugs on intimal hyperplasia (IH) of the anastomotic site is particularly attractive.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are several strategies for secondary intervention to salvage SVG bypass failure, and it is reported DCB usage prevents restenosis and prolongs the time period for re-intervention. 3 However, some studies reported that the clinical results following DCB use did not differ from conventional therapy. 4 Best alternative therapy for refractory SVG restenosis remains controversial.…”
mentioning
confidence: 99%